Association Between Platelet Levels on Admission and 90-day Mortality in Patients With Exertional Heatstroke, a 10 Years Cohort Study - Zhong, Li; Wu, Ming; Ji, Jingjing; Wang, Conglin; Liu, Zhifeng (Frontiers in Medicine, 2021)
Backgroud: Heatstroke is a common clinical symptom in summer with high mortality requiring identification of appropriate and rapid methods of assessment. Method: This is a retrospective study that included the recent 10 years clinical data of heatstroke patients. A total of n=186 patients were included in this study and grouped based on platelet (PLT) abnormality observed on admission. Results: In the study group, n=120 patients (64.5%) patients had normal PLT and n=66 patients (35.5%) had abnormal PLT. Compared with PLT-normal group, PLT-abnormal group had higher Acute Physiology and Chronic Health Evaluation II ( APACHE II) scores [median 15.0 (IQR 11.5-21.5) vs. 9.0 (IQR 7.0-12.5)] and SOFA scores [median 6.0 (IQR 4.0-10.0) vs. 2.0 (IQR 2.0-4.0)], lower Sequential Organ Failure Assessment (GCS )[median 8.0 (IQR 5.0-12.0) vs. 13.0 (IQR 9.0-14.0)]. The PLT-abnormal group had severe organ damage, including damage to the coagulation system, liver, and kidney (all p<0.05). Significant differences were noted in 90-day survival between the two groups even after correction for Age, GCS, White blood cell count (WBC), Neutrophil, International normalized ratio (INR), Activated partial thromboplastin time (APTT), Procalcitonin (PCT), Alanine aminotransferase (ALT), Creatine (CR), D-Dime(D-D) (Before correction P<0.001; After correction P=0.009).The area under the ROC curve for the prediction of mortality based on PLT was 80.7% (95% CI 0.726-0.888, P<0.001), the optimal cutoff value was 94, the sensitivity was 77.3%, and the specificity was 82.6%. Conclusion: Patients with heatstroke with platelet abnormalities during admission have more severe organ impairment and a lower 90-day survival rate even when adjusted for other factors.